2020
DOI: 10.1016/j.biopsych.2020.02.1179
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Kv3.1 Activity in Dentate Gyrus Parvalbumin Cells Induces Vulnerability to Depression

Abstract: BACKGROUND: Parvalbumin (PV)-expressing interneurons are important for cognitive and emotional behaviors. These neurons express high levels of p11, a protein associated with depression and action of antidepressants. METHODS: We characterized the behavioral response to subthreshold stress in mice with conditional deletion of p11 in PV cells. Using chemogenetics, viral-mediated gene delivery, and a specific ion channel agonist, we studied the role of dentate gyrus PV cells in regulating anxiety-like behavior and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…However, we showed that inhibition of dMCs results in ventral GC hyperexcitability, which has been causally linked to elevation of anxiety responses 30 . Consistent with this, direct manipulations of PV + BC activity in the DG altered anxiety-like behaviors 31,32 . Therefore, dMCs may regulate anxiety-like behaviors with longitudinal control of the DG network, primarily through PV + BCs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, we showed that inhibition of dMCs results in ventral GC hyperexcitability, which has been causally linked to elevation of anxiety responses 30 . Consistent with this, direct manipulations of PV + BC activity in the DG altered anxiety-like behaviors 31,32 . Therefore, dMCs may regulate anxiety-like behaviors with longitudinal control of the DG network, primarily through PV + BCs.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, it is important that dMCs provide indirect inhibition onto GCs through PV + BCs. In fact, dysregulation in the high-frequency ring of PV + BCs impairs spatial pattern separation in the DG 31 . Supporting this idea, computational modeling suggests that inhibition of MC-to-BC connections resulted in the recruitment of signi cantly more GCs in response to simulated entorhinal input.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, we propose in this study to define the relationship between the expression of the Kv3.1b and the serotonergic activity of the 1C11 cell line, using fluoxetine, their common modulator. 1C11 is a murine serotonergic cell line from neuronal stem cells and may undergo either serotoninergic or noradrenergic differentiation upon induction [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…AUT00063 has also been shown to improve auditory synchronization and support more accurate decoding of temporal sound features in the inferior colliculus and auditory cortex in adult mice with a nearcomplete loss of auditory nerve afferent synapses in the contralateral ear [197], rendering K V 3.1 modulators an attractive candidate for pharmaceutical targeting against fast auditory processing deficits due to ARHL. Furthermore, antidepressants, such as p11, have been shown to control K V 3.1 expression level and intracellular localization in PV+ interneurons of the hippocampus [202]. With reduced K V 3.1 levels, the capacity of PV+ interneurons to adapt to high-frequency firing is abolished [202], underscoring the crucial role that sustained expression levels of K V 3.1 may have over age for preserving temporal auditory processing and speech discrimination.…”
Section: K + Channels As Therapeutic Targets Against Arhlmentioning
confidence: 99%
“…Furthermore, antidepressants, such as p11, have been shown to control K V 3.1 expression level and intracellular localization in PV+ interneurons of the hippocampus [202]. With reduced K V 3.1 levels, the capacity of PV+ interneurons to adapt to high-frequency firing is abolished [202], underscoring the crucial role that sustained expression levels of K V 3.1 may have over age for preserving temporal auditory processing and speech discrimination. Importantly, the high metabolic vulnerability of particular PV+ interneuron synapses [203] should be reconsidered in the context of required sustained K V 3.1 channels for its proper function in the ascending auditory pathway.…”
Section: K + Channels As Therapeutic Targets Against Arhlmentioning
confidence: 99%